Microestrutura, textura cristalográfica e propriedades de ligas de magnésio processadas por extrusão em canal iguais angular - Barros Neto, João Rodrigues de (2020)
Currently, there is a great research effort to develop new and cleaner technologies, such as the use of renewable fuels in order to reduce emissions of polluting gases. The use of hydrogen as an energy carrier has been shown to be very attractive, since the product of its combustion is only water and its energy per unit mass is at least 3 to 5 times greater than any other chemical fuel. However, one of the main challenges of its use is in its safe and effective storage, taking into account several simultaneous criteria, e. g. how to obtain the highest possible volumetric and gravimetric density, and enable its reversibility with high cyclability and low material and processing costs. Metal hydrides such as MgH2 are considered promising ways of storing hydrogen in the solid state, being safer and more effective than using hydrogen gas under high pressure (around 700 bar) or liquid (21 K). In order to improve the properties of hydrogen storage materials, particularly those based on Mg, severe plastic deformation processes have been studied, such as ECAP (equal channel angular pressing), which refines considerably the microstructure, making easier its reaction with hydrogen. Another characteristic of the processed material that can contribute markedly is the development of an adequate crystallographic texture. In this work, commercially pure Mg and EZ33 alloy were processed under different ECAP conditions. Microstructural analyzes, study of the crystallographic texture, measurement of hydrogenation and mechanical properties were carried out. The results showed that the material taken from different sections (from the same processed specimen) had different hydrogen storage properties, even after the filing process. The sections that had less grain refining, less density of defects and crystallographic textures closer to the basal {0002}, showed to have the best hydrogen absorption and desorption properties. The results of hydrogen absorption/desorption kinetics were promising when compared to other preparation processes such as HEBM (high-energy ball milling).